The role of organic and inorganic soil amendments on soil physicochemical properties and wheat (Triticum aestivum L.) agronomic performance in Semi-arid North-Central Namibia: A Review - Haufiku, Anna Maria; Ausiku, Petrus Ausiku; Huttunen, Sanna (Springer Science and Business Media LLC, 2026)
Poor soil fertility in semi-arid and arid regions has been identified as a major challenge affecting agricultural productivity, leading to poverty and low food security among smallholder farmers. Soil amendments, especially organic, have gained popularity in recent years because they improve soil fertility, reduce greenhouse gas emissions and improve crop production. In Namibia, wheat is an important cereal crop that substantially contributes to developing the agricultural sector and improving farm household food security, particularly. The literature review was undertaken to assess the effects of soil amendments on soil physical and chemical properties, wheat growth, and yield across various agro-climatic conditions, with a particular emphasis on evaluating the potential of biochar and compost to enhance wheat production in the semi-arid Namibia. Most of the literature search with keywords “soil amendments, biochar, compost, soil fertility, soil management, sustainable agriculture, wheat, semi-arid” was conducted on online databases such as Google Scholar, Wiley, Scopus, and Science Direct (mostly with the range of years from 2010 to 2024). The selection of scientific articles was based on title, abstract and content. Based on published research articles, the conversion of locally available feedstocks, such as crop residues, forest biomass, and kitchen and animal wastes, into organic soil amendments like biochar, compost and vermicompost may also be necessary in smallholder farming systems. Additionally, biochar use may have applications in tree nursery production and speciality-crop management. Thus, biochar can make a substantial contribution to sustainable agriculture. The review concluded that organic soil amendments can be effective components of chemical fertilizers, contributing to lower nutrient losses in the soil and reducing environmental impacts in a sustainable manner.